The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/healthcare9111464
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Predicting the Risk for Childhood Asthma Using Prenatal, Perinatal, Postnatal and Environmental Factors

Abstract: The prevalence rate for childhood asthma and its associated risk factors vary significantly across countries and regions. In the case of Morocco, the scarcity of available medical data makes scientific research on diseases such as asthma very challenging. In this paper, we build machine learning models to predict the occurrence of childhood asthma using data from a prospective study of 202 children with and without asthma. The association between different factors and asthma diagnosis is first assessed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Conversely, Dalla Costa et al have demonstrated that the type of delivery and the type of lactation affect the age of onset of MS. In particular, caesarean section and formula milk anticipate the age of onset of the disease [196]. Interpretation of these results could be influenced by the fact that both caesarean section and formula milk lead to an imbalance in the development of the microbiota, which would participate in the alteration of the immune system, culminating in the onset of an autoimmune pathology such as MS.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Dalla Costa et al have demonstrated that the type of delivery and the type of lactation affect the age of onset of MS. In particular, caesarean section and formula milk anticipate the age of onset of the disease [196]. Interpretation of these results could be influenced by the fact that both caesarean section and formula milk lead to an imbalance in the development of the microbiota, which would participate in the alteration of the immune system, culminating in the onset of an autoimmune pathology such as MS.…”
Section: Discussionmentioning
confidence: 99%
“…Decision trees were successfully used to associate demographic features with allergic outcomes during the allergic march to assess the possibility of allergy transfer to asthma in children with respect to race [36]. Decision trees were also used to explore the relationship between various risk factors and childhood asthma [37]. Neural networks were used for a cough sound analysis to differentiate pneumonia from asthma [38].…”
Section: Deductive Content Analysis Of the Most Prolific Machine Lear...mentioning
confidence: 99%
“…The recent development of artificial intelligence techniques (especially machine learning and deep learning), as well as the data availability of detailed patient information, empowers the prediction and risk assessment of various chronic diseases. For example, machine learning has been employed in predicting cardiovascular diseases (7)(8)(9). While many machine learning models have been successfully built for predicting asthma exacerbations among asthmatic patients (10)(11)(12)(13)(14)(15)(16), fewer studies have been conducted on predicting asthma risk using various datasets especially publicly available data, such as the 2019 Michigan BRFSS data and a small dataset of 202 children from Ibn Sina Hospital Center in Morocco (7,8).…”
Section: Introductionmentioning
confidence: 99%